Model Latihan Berbasis Permainan Meningkatkan Daya Tahan Cardiorespiratory Atlet Pencaksilat Usia SMP - Hidayatulloh, Dede Taufik; Asmawi, Moch; Sujiono, Bambang (UIR Press, 2018)
In this decade, there are a lot of international researchers discuss about Physical Activity. Indonesia is a country which has big overweight problem and non-infection disease which attacked its citizen. Both of those problems are the impacts of low physical activity. This study aimed to investigate the level of students’ physical activity. International Physical Activity Questionnaire (IPAQ) was distributed to investigate the level of students’ physical activity. It had three scale levels such as vigorous activity, moderat activity, and walking activity in last seven days. There were 128 students participated in this study. The result proved that there is no difference activity between male and female students. Mean score of male students was 1506.61 MET (min/week), and female students’ mean score was1015.85 MET (min/week). Generally, male students do physical activity higher than female. The finding shown that overall, the students’ physical activity is still low, so there must be an appropriate effort to revise their health and life style.